Tantangan Siswa Sekolah Dasar dalam Belajar Bahasa Inggris: Sebuah Refleksi Untuk Kurikulum Merdeka dari Daerah Pedesaan di Kalimantan Barat - Lestari, Sri; Surtikanti, Monika Widyastuti (Efektor, 2024)
English is a foreign language taught in educational units throughout Indonesia. Therefore, in learning English, of course, students face a variety of challenges. This study aims to discover the challenges students of SDN 14 Sungai Ambawang face in learning English and to identify any factors that influence the challenges students face in learning English. The research method used is qualitative, with a case study research design. Data collection is done through observation, questionnaires, and interviews. Data analysis techniques applied interactive models, including data collection, condensation, display, and drawing and verifying conclusions. This study found that several challenges and factors cause elementary school students to learn English as a foreign language, namely difficulty in understanding, writing, listening, and pronouncing words. The causes include a lack of self-confidence, a lack of support from the neighborhood school, a lack of home support, and a lack of learning facilities. Future research could expand the broader context of English teaching as a compulsory subject.